Medical Records Search Application Design Outpatient at RSI Ibnu Sina Padang Year 2023 - Alfauzain; Mughni Dhastin; Ade Wisandra; Mila Sari (Miracle Journal Get Press, 2024)
The problem at RSI Ibnu Sina Padang in 2023 is that the search for medical records is always done manually with the time needed for 1 medical record ± 10 minutes, this is because the medical records are not specified or scattered. The purpose of this study is to find out the design of an outpatient medical record search application at RSI Ibnu Sina Padang in 2023. By adopting the type of research, namely Research & Development (R&D) with the prototype development method. The research was conducted from January to July 2023. The number of informants was 5 people, namely 5 runner officers. Conduct data analysis of potentials and problems, collect data, design products, validate designs, improve designs, and test products. The results showed that the process flow for filling in components, especially in the form of searching was done manually which included outpatient registration proof sheets. Application design can be fully implemented. The test results show that the existing components are in accordance with the hospital format and the application of the search process is faster and more efficient than manual search. Based on the results of the study, it was concluded that the design of the outpatient medical record storage information system was in accordance with the hospital format. It is hoped that this research application design can be used in hospitals and this research can be continued by other researchers.